Analysis Of Diet With The Incidence Of PEB In Pregnant Women At Murjani Sampit Hospital Kotawaringin Timur Regency Kalimantan Tengah Province - Tety Ripursari; Riza Tsalatsatul Mufida; Dina Oktavianty (Journal for Research in Public Health, 2023)
The high incidence of preeclampsia and eclampsia in developing countries is associated with low socioeconomic status, which has an impact on the inability of family members to buy and provide nutritious food during pregnancy. The purpose of this study was to determine the relationship between diet and the incidence of PEB in pregnant women at Murjani Sampit Hospital, Kotawaringin Timur Regency, Kalimantan Tengah Province. The design of this study is a correlational study with a cross sectional approach. Respondents were taken by accidental sampling technique with a sample of 30 people. The results of statistical tests using Chi Square. The results showed that most of the respondents as many as 22 (73%) in the category of good diet and almost all respondents as many as 26 (87%) in the category of no PEB. The results of data analysis show that the significance level is 0.000 < = 0.05 so that H0 is rejected and H1 is accepted. Thus, there is a relationship between diet and the incidence of PEB in pregnant women at Murjani Sampit Hospital, Kotawaringin Timur Regency, Kalimantan Tengah Province. Recommended that pregnant women can avoid fatty foods and consuming snacks or foods that are high in salt.